Engineering a pure and stable heterodimeric IgA for the development of multispecific therapeutics - Florian Heinkel; Meghan M. Verstraete; Siran Cao; Janessa Li; Patrick Farber; Elizabeth Stangle; Begonia Silva-Moreno; Fangni Peng; Surjit Dixit; Martin J. Boulanger; Thomas Spreter Von Kreudenstein; Eric Escobar-Cabrera (Taylor & Francis Group, 2022)
Immunoglobulin G (IgG) has served as a traditional framework for antibody-based biology, and engineering approaches for creating multispecific therapeutics have greatly expanded its applicability. Despite these developments, there are limits to the functionality of IgG with respect to effector cells that can be activated and paratope valency that can be obtained. Other Ig isotypes have distinct functions that can engage and activate different effector cells, and some can be found naturally in higher-order assemblies. In an effort to expand the repertoire of multispecific designs for other antibody isotypes, we present here engineering of the first heterodimeric IgA Fc that can be produced at high purity with native IgA-like thermal stability. The crystal structure confirmed the accuracy of the in silico model used for engineering and that the mutations introduced at the CH3 interface do not perturb the overall IgA Fc structure. Affinity measurements and on-cell neutrophil binding demonstrated that the heterodimeric IgA Fc retains the ability to bind FcαRI, an important prerequisite for IgA-based therapeutics designed to interact with effector cells, such as neutrophils. Given the ability of IgA antibodies to multimerize via interaction with the J-chain, the designs presented here could also be used to generate multispecific, multimeric scaffolds that leverage valency to increase clustering and specificity via avidity. Taken together, the newly developed heterodimeric IgA Fc platform allows for the development of novel, multifunctional, and multimeric molecules that have the potential to transform the next generation of antibody therapeutics.Abbreviations CE-SDS: capillary electrophoresis sodium dodecyl sulfate; DSC: differential scanning calorimetry; FACS: fluorescence-activated cell sorting; FSA: full-sized antibody; Her2: human epidermal growth factor receptor 2; MFI: mean fluorescent intensity; OAA: one-armed antibody; PBS: phosphate-buffered saline; PDB: Protein Data Bank; SEC: size-exclusion chromatography; prepSEC (preparative SEC); RMSD: root-mean-square deviation; RU: resonance units; SPR: surface plasmon resonance; TAA: tumor-associated antigen; WT: wild-type.